2012
DOI: 10.3727/108354212x13330406124214
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Domestic Tourism for Urban and Semiurban Populations Around Nairobi National Park, Kenya

Abstract: †kenya Wildlife Service, nairobi, kenya ‡Department of tourism and tour Operations Management, Moi University-kenya, eldoret, kenya tourism is a very important source for foreign revenue for kenya. But most of this revenue is from international tourists. however, international tourists cannot always support the tourism industry, especially in years of economic, political, and social turmoil. A vibrant domestic tourism can cushion the industry from fluctuations of the international tourism market and bring stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 9 publications
(9 reference statements)
1
19
0
Order By: Relevance
“…They also lack information specific to each country on why domestic tourism has not improved as in developed nations. More research is needed in this area in Eastern Africa countries so as to have specific actions that address key constraints to domestic and regional tourism growth to compliment international tourism especially in low season and at times when for one reason or another, tourists from international markets cannot come [40].…”
Section: Poor Development and Activities In Domestic And Regional Toumentioning
confidence: 99%
See 3 more Smart Citations
“…They also lack information specific to each country on why domestic tourism has not improved as in developed nations. More research is needed in this area in Eastern Africa countries so as to have specific actions that address key constraints to domestic and regional tourism growth to compliment international tourism especially in low season and at times when for one reason or another, tourists from international markets cannot come [40].…”
Section: Poor Development and Activities In Domestic And Regional Toumentioning
confidence: 99%
“…The lands outside the parks are crucial to wildlife; they serve as dispersal areas. These areas are threatened with increasing land sub-division, agricultural expansion and unplanned development of tourist accommodation, thus increasing human-wildlife conflicts [16,19,22,40]. In Kenya for example, it is alleged that over 70 percent of the wild animals live outside official protection areas.…”
Section: Cost Of Conservation and Human-wildlife Conflictsmentioning
confidence: 99%
See 2 more Smart Citations
“…A study on the Kafue National Park in Zambia (Thapa, 2012) found that international and domestic visitor segments indicated varying degrees of perceived constraints, with structural constraints being more common among domestic visitors. In a study on factors influencing the surrounding domestic population to visit Nairobi National Park in Kenya (Okello et al, 2012), it was found that majority (66%) of the community had visited the park. Even though the lack of free time (structural), lack of interest in wildlife (personal), or the thinking that protected areas in Kenya were meant for foreign tourists (personal), were not hindrances to local community visiting the parks, they noted that key constraints were lack of extra disposable income (structural), high cost of food and hospitality services inside the park for local communities (structural), and poor marketing of parks especially targeting local Kenyans (structural).…”
Section: Constraints To Visiting National Parksmentioning
confidence: 99%